The critical edition of “Suspicious” by Julian Ursyn Niemcewicz (Part II, Act IV-V) - Rojewska, Magdalena (Melusine. Old Literature and Culture, 2026)
The subject of the study is the edition of “Suspicious” (Podejrzliwy) by Julian Ursyn Niemcewicz (Warsaw 1831). This is the late political comedy by the author of “The return of the deputy” (Powrót posła), which in artistic way registers events that are a consequence of the tsarist policy of Alexander I towards Poles after 1818. In addition to the main plot intrigue, the comedy brings a picture of extensive espionage network managed by senator Nowosilcow and his supporters. “Suspicious” was written between September 9 and November 5, 1819, but some of the scenes were added only after 1822, once the censorship blocked attempts to introduce comedy on the stage of the National Theater. It was then that the events related to the Vilnius investigation and Filaret’s process took place (these events are present in the added scenes). The basis for the edition was the first edition of the comedy published in 1831, enriched by three scenes of the first act comparing to other broadcasts. It was compared with the autograph of the work preserved in the Raczyński’s Library in Poznań (reference number 41) and a manuscript copy made for the stage and sent to the censorship in 1821.